Efficacy of Psychoeducation and Cognitive Rehabilitation After Mild Traumatic Brain Injury for Preventing Post-concussional Syndrome in Individuals With High Risk of Poor Prognosis: A Randomized Clinical Trial - Caplain, Sophie; Chenuc, Gaelle; Blancho, Sophie; Marque, Sébastien; Aghakhani, Nozar (Frontiers in Neurology, 2019)
Unfavourable outcomes (UO) are seen in 15 to 20% of patients with mild traumatic brain injury (mTBI). Early identification of patients at risk for UO is crucial for suitable management to be initiated, increasing their chances for a return to a normal life. We previously developed a diagnostic tool enabling early identification (8 to 21 days after the injury) of patients likely to develop UO. In the present study, we examine the value and beneficial effects of early multidimensional management (MM) on prognosis. We used our diagnostic tool to classify 221 mTBI patients as UO (97) or FO (favourable outcome) (124). Patients whose initial risk factors point to UO are at risk of developing post-concussion syndrome (PCS). We randomized UO patients into 2 groups: a group that underwent MM (cognitive-behavioural rehabilitation) (34) and a group with no specific management (46). At 6 months, these 2 groups were compared and the impact of MM on outcome was assessed. Among patients initially classified as FO (101), 95% had FO at 6 months and only 5 had PCS as defined by DSM-IV classification. Of the UO patients who received MM, 94% had no PCS 6 months after injury, whereas 52% of the UO patients who did not receive MM had persistent PCS. The effect of MM on the recovery of patients at 6 months, once adjusted for the main confounding factors, was statistically significant (p<0.001). These results show that the initiation of MM after early identification of at-risk mTBI patients can considerably improves their prognosis.